2021
DOI: 10.3389/fnut.2021.689214
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Correlation With Anthropometric and Biochemical Indicators of Cardiometabolic Risk in Serbian Underground Coal Miners in 2016

Abstract: The status of vitamin D in underground working coal miners and its association with their cardiometabolic health is rarely studied. This study aimed to examine vitamin D (VitD) status in Serbian underground coal miners and to correlate it with anthropometric and laboratory indicators of cardiometabolic risk. Nutritional data (food frequency questionnaire, FFQ, and two times repeated 24 h recall), anthropometric data (including segmental analysis by bio-impedance analyzer TANITA BC-545N), arterial tension, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
(201 reference statements)
1
1
0
Order By: Relevance
“…Additionally, the percentage of those with vigorous physical activity, heavy alcohol consumption, and regular smoking was higher in the group of miners. Interestingly, miners exhibited the highest serum 25(OH)D levels, which is in accordance with some literature data [ 57 ]. One plausible explanation is the strenuous physical work undertaken by miners, leading to increased lipolysis and release of 25(OH)D from fat and muscle depots [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the percentage of those with vigorous physical activity, heavy alcohol consumption, and regular smoking was higher in the group of miners. Interestingly, miners exhibited the highest serum 25(OH)D levels, which is in accordance with some literature data [ 57 ]. One plausible explanation is the strenuous physical work undertaken by miners, leading to increased lipolysis and release of 25(OH)D from fat and muscle depots [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the inhibitor significantly reduced obesity in MRL/LPR mice. Other studies 17,18 have revealed a correlation between VitD deficiency and tissue fat thickness. That supplementation with VitD3 can reduce weight gain and fat accumulation in mice has confirmed, and the study showed that the body weight of C57BL/6 mice on a high‐fat diet changed significantly after continuous supplementation with VitD3 for 10 weeks 19,20 .…”
Section: Discussionmentioning
confidence: 90%